2022
DOI: 10.12998/wjcc.v10.i36.13321
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic leakage in rectal cancer surgery: Retrospective analysis of risk factors

Abstract: BACKGROUND Anastomotic leakage (AL) after restorative surgery for rectal cancer (RC) is associated with significant morbidity and mortality. AIM To ascertain the risk factors by examining cases of AL in rectal surgery in this retrospective cohort study. METHODS To identify risk factors for AL, a review of 583 patients who underwent rectal resection with a double-stapling colorectal anastomosis between January 2007 and January 2022 was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
8
1
Order By: Relevance
“…Allaix et al [ 26 ] reported that intraoperative ALTs enable the detection of AL defects after laparoscopic left-sided colon resection, which could be effectively managed intraoperatively, leading to a significantly lower risk of postoperative AL. Previous studies have shown higher preoperative chemoradiotherapy rates (52.3%–67.4%) than those reported in our study [ 2 13 26 27 ]. The main reason was that we omitted preoperative chemoradiotherapy in higher rectal cancer [ 28 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Allaix et al [ 26 ] reported that intraoperative ALTs enable the detection of AL defects after laparoscopic left-sided colon resection, which could be effectively managed intraoperatively, leading to a significantly lower risk of postoperative AL. Previous studies have shown higher preoperative chemoradiotherapy rates (52.3%–67.4%) than those reported in our study [ 2 13 26 27 ]. The main reason was that we omitted preoperative chemoradiotherapy in higher rectal cancer [ 28 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Complications from colorectal anastomosis leaks are serious issues following sphincter preservation surgery. Previous reports indicate that the anastomotic leak rate ranges from 3% to 20%, significantly increasing the risk of postoperative death by up to 27%, as well as the risk of permanent colostomies and cancer recurrence [ 11 , 12 , 19 , 20 ]. Treatment of these complications has a high success rate but can still leave severe and lasting sequelae [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these patients must also undergo surgery to close the ileostomy, which carries many risks [ 22 , 25 - 27 ]. The research by Brisinda et al showed that ileostomy did not necessarily help reduce the anastomotic leak rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this objective is likely impossible because the occurrence of anastomotic leakage depends on various factors involving non-modifiable risk factors such as patient characteristics and comorbidities (age, gender, ASA score, diabetes, tobacco use, corticosteroid use, administration of neoadjuvant treatments), as well as histopathological factors related to the disease that required the intervention [ 2 4 ]. Potentially modifiable risk factors to reduce the rate of this complication have been associated with optimizing preoperative albumin and haemoglobin levels, normalizing blood glucose levels, using minimally invasive surgical techniques, precise surgical timing [ 3 ], high ligation of the inferior mesenteric artery [ 5 ] and the use of a refined surgical technique [ 6 ].…”
Section: Introductionmentioning
confidence: 99%